Особливості виконання кошторису в бюджетних устновах - Демчук, Олена Миколаївна; Демчук, Елена Николаевна; Demchuk, Оlena (My University, 2018)
UK: У статті проаналізовано показники виконання доходної та видаткової частини загального та спеціального фондів кошторису вищого навчального заклад, на прикладі Таврійського державного агротехнологічного університет. Проведено аналіз видатків вищого навчального закладу в розрізі кодів економічної класифікації. Визначено напрямки оптимізації витрат та залучення додаткових надходжень для фінансування видатків, пов’язаних з діяльністю установи. EN: Today, budget institutions that operate under difficult economic conditions and with a budget deficit require a flexible system of measures aimed at compliance with the law on the effective and targeted use of budget funds, both for the general and special fund. The main source of information for monitoring the implementation of the budget is the accounting data. The main research material. Let's consider the order of execution of the estimate by the institution of education on the example of the Tavria State Agrotechnological University. Higher educational institutions of Ukraine of state and communal ownership are financed by the budget-based method on the basis of estimates, which approve revenues and provide the authority to carry out expenditures for the performance of their functional duties. They have the right to exercise their activities only within the limits of budget allocations, which are approved by the following documents: estimates; plans of general budget funds allocations; plans for granting credits from the gen-eral fund of the budget; special fund plans. And for higher educational establishments, scientific institutions and health facilities also within the limits of budgetary allocations, approved by plans of use of budgetary funds and monthly plans of use of budgetary funds.
Features of implementation of budget installations
Keywords: кошторис; виконання кошторису; загальний фонд; спеціальний фонд; доходи; видатки; розпорядники бюджетних коштів; budget; execution of estimates; general fund; special fund; expenditures; spending units